The Salaf Scholars’ Response towards differences of Legal Opinion in Islamic Law - Suraji Suraji (International Journal of Social Science and Religion (IJSSR), 2023)
A Prophetic hadith states that the best of people were in my time, and then the time after that, and then the time after that. Of course, it is a question for Muslims or non-Muslims, why the Prophet stated it. The above statement can certainly be seen from the ethics and academic reasoning of the post-Prophet generation. Maturity in arguing and accepting criticism is seen in the legal opinion of Ulama, especially in scientific ethics when there are differences of opinion with mutual respect and respect and usually concluded with a sentence if it is right then it is my mazhab and if it is wrong please leave it.